2009
DOI: 10.1161/circresaha.109.195040
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Identification and Functional Characterization of a Mitochondrial Sulfonylurea Receptor 2 Splice Variant Generated by Intraexonic Splicing

Abstract: Rationale: Cardioprotective pathways may involve a mitochondrial ATP-sensitive potassium (mitoK ATP ) channel but its composition is not fully understood. Objective: We hypothesized that the mitoK ATP channel contains a sulfonylurea receptor (SUR)2 regulatory subunit and aimed to identify the molecular structure. Methods and Results: Western blot analysis in cardiac mitochondria detected a 55-kDa mitochondrial SUR2 (mitoSUR2) short form, 2 additional short forms (28 and 68 kDa), and a 130-kDa long form. RACE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 56 publications
(52 reference statements)
1
89
3
3
Order By: Relevance
“…Such a pattern is common in the cardioprotection field; for example, ablation of STAT3 abolishes protection by IPC while having no impact on baseline I/R injury (29,40). It is also notable that genetic ablation of SUR2 increases resistance to I/R injury (30), but this may be due to expression of short-form SUR2 splice variants in the SUR2 Ϫ/Ϫ knockout mouse, which are thought to independently mediate cardioprotection (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…Such a pattern is common in the cardioprotection field; for example, ablation of STAT3 abolishes protection by IPC while having no impact on baseline I/R injury (29,40). It is also notable that genetic ablation of SUR2 increases resistance to I/R injury (30), but this may be due to expression of short-form SUR2 splice variants in the SUR2 Ϫ/Ϫ knockout mouse, which are thought to independently mediate cardioprotection (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, low-molecular-weight SUR2 isoforms have been identified that may be components of the mitochondrial K ATP channel. When heterologously expressed, a 55 kDa SUR2 splice variant colocalizes with mitoTracker dyes in COS1 cells (901). However, when coexpressed with Kir6.x, patch-clamp methods demonstrate the presence of plasmalemmal K ATP channels that are blocked by millimolar ATP levels but are practically insensitive to pinacidil, diazoxide, or glibenclamide (3).…”
Section: Molecular Compositionmentioning
confidence: 99%
“…Murine cardiac myocytes express both full-length (130 kDa) and short (28,55, and 68 kDa) SUR2 forms (32,45). Fulllength SUR2 is absent, whereas all three short forms are present, in SUR2 nl mouse cardiac myocytes (32).…”
Section: Discussionmentioning
confidence: 99%